Pengaruh Progressive Muscle Relaxation Terhadap Penurunan Kecemasan Pasien Kanker Yang Akan Menjalani Kemoterapi Di Ruang Oncology Murni Teguh Memorial Hospital - Lumban Toruan, Lestary; Silaen, Harsudianto (Universitas Murni Teguh, 2024)
One of the therapies for cancer is chemotherapy and is an effective method of choice, especially for advanced stages. However, chemotherapy often causes side effects including nausea and vomiting, fluid-electrolyte balance disorders and stomatitis, which makes patients anxious. Progressive muscle relaxation technique is thought to reduce anxiety in patients undergoing chemotherapy. This study aims to determine the effect of progressive muscle relaxation on reducing anxiety in cancer patients undergoing chemotherapy. This research is quasi-experimental research using a one group pretest and posttest design and the sample is 31 people. The data used are primary data and secondary data. The analysis was carried out univariate and bivariate using a paired sample t-test with a 95% confidence level (0.05). The results of this study indicate that the majority of cancer patients who will undergo chemotherapy before being given progressive muscle relaxation (pretest) treatment experience moderate anxiety (54.8%), and after being treated with progressive muscle relaxation (posttest) the majority experience mild anxiety (61.3%). There is an effect of progressive muscle relaxation on the anxiety of cancer patients who will undergo chemotherapy in the Oncology unit Murni Teguh Memorial Hospital, or there is a difference in the anxiety of patients before and after being given progressive muscle relaxation, with a value of t-count (11,728) > t-table (2,040). and p value = 0.000 <0.05. Progressive muscle relaxation is effective for reducing anxiety in cancer patients who will undergo chemotherapy. It is recommended that Murni Teguh Memorial Hospital make policies and SOPs regarding progressive muscle relaxation treatment so that it can be practiced routinely for patients who will undergo chemotherapy. Abstrak Salah satu terapi untuk penyakit kanker adalah kemoterapi dan menjadi metode pilihan yang efektif terutama untuk stadium lanjut. Akan tetapi, kemoterapi sering menimbulkan efek samping diantaranya mual muntah, gangguan keseimbangan cairan elektrolit dan stomatitis, yang membuat pasien menjadi cemas. Teknik progressive muscle relaxation diduga dapat menurunkan kecemasan pasien yang akan menjalani kemoterapi. Untuk mengetahui pengaruh progressive muscle relaxation terhadap penurunan kecemasan pasien kanker yang akan menjalani kemoterapi. Penelitian ini adalah penelitian kuasi eksperimen menggunakan desain one group pretest and posttest design dan sampel diperoleh 31 orang. Data yang digunakan data primer dan data sekunder. Analisis dilakukan secara univariat dan bivariat menggunakan uji dua sampel berpasangan (paired sample t-test) dengan tingkat kepercayaan 95% (0,05). Hasil penelitian ini menunjukkan bahwa kecemasan pasien kanker yang akan menjalani kemoterapi sebelum diberi perlakuan progressive muscle relaxation (pretest) mayoritas mengalami cemas sedang (54,8%), dan setelah diberi perlakuan progressive muscle relaxation (posttest) mayoritas mengalami cemas ringan (61,3%). Terdapat pengaruh progressive muscle relaxation terhadap kecemasan pasien kanker yang akan menjalani kemoterapi di Ruang Oncology Murni Teguh Memorial Hospital, atau ada perbedaan rasa cemas pasien sebelum dan setelah diberi progressive muscle relaxation, dengan nilai t-hitung (11,728) > t-tabel (2,040) dan nilai p=0,000 <0,05. Progressive muscle relaxation efektif untuk menurunkan kecemasan pasien kanker yang akan menjalani kemoterapi. Disarankan pihak Murni Teguh Memorial Hospital untuk membuat kebijakan dan SOP tentang perlakuan progressive muscle relaxation agar dapat dipraktekkan secara rutin kepada pasien yang akan menjalani kemoterapi.